Structural Reliability of AlGaN/GaN High Electron Mobility Transistors - Udai Prakash; Dr. Navaid Z. Rizvi; Herman-Al-Ayubi (Journal of Electronic Design Engineering, 2019)
The GaN devices have significant advantages in terms of power density, characteristics and voltage range based on conventional compound semiconductors or Silicon. The aim of this work is to observe and analyze the results of 3D Structural Reliability of AlGaN/GaN HEMT structure. The work is mostly focused on the coupled behavior of Aluminum Gallium-nitride (AlGaN)/ Gallium-nitride (GaN) high-electron- mobility transistors (HEMTs). The modeling have to be performed considering to the various coupled properties like piezo- electric effect, inverse piezoelectric effect, mechanical stress, Joule heating effect etc. The Structural Reliability with modeling of AlGaN/GaN HEMTs is performed using ANSYS and MATLAB simulation software.